Parasitic infections - challenges in treatment - de Silva, N.R. (Sri Lanka College of Microbiologists, 2012)
Professor of Parasitology, Department of Parasitology, Faculty of Medicine, University of Kelaniya, Ragama The term 'parasitic infections' includes infection by uni-cellular protozoan organisms as well as multi-cellular helminths. Many of these organisms have complex life-cycles with several morphological forms and sophisticated mechanisms to evade the host's immune response. Challenges in the treatment of parasitic infections may arise due to a variety of different reasons. It may be an infection where it is difficult to make a conclusive diagnosis in the first place. Examples include toxoplasmosis and hydatidosis, infections that are confined to the tissues, and a conclusive laboratory diagnosis is notoriously difficult to establish. Other parasitic infection are difficult to treat simply because of the lack of effective drugs {e.g. cryptosporidiosis) or because the available drugs are difficult to administer and have toxic adverse effects (e.g. visceral ieishmaniasis, human African trypanosomiasis). There are yet other infections that are challenging to treat because the pathogen has a complex life cycle that involves auto-infection. Strongyloidiasis and entero-biasis are examples of such infections where recurrent re-infection resulting from auto-infection may make it necessary to repeat treatment several times over. Finally, the emergence of drug resistance could also mean that the infection may be a challenge to treat. Fatciparum malaria is a prime example of an infection that can be very difficult to treat because the pathogen is resistant to many different drugs. The presentation will focus on two intestinal parasitic infections that can be particularly challenging to treat: Strongyloidiasis and cryptosporidiosis. Both infections are briefly reviewed under the following aspects: life cycle and morphology; epidemiology; clinical manife¬stations; pathogenesis and immunity; diagnosis; treatment and prognosis. was implemented. From October 2010 to July 2011, 30-day mortality fell significantly, 118/668 (17.7%). BHRUT is one of 3 centres to have published data demonstrating a reduction in mortality through a continuous cycle of regular bacteraemia surveillance and implementation of a quality improvement programme.
Abstracts of the plenary lectures and symposia - The bulletin of the Sri Lanka College of Microbiologists, 29th-30th August 2012, Colombo
Keywords: Parasitic infections